KRITIK PENGARANG TERHADAP EKSPLOITASI ALAM DALAM NOVEL PEREMPUAN YANG MENUNGGU DI LORONG MENUJU LAUT KARYA DIAN PURNOMO: KAJIAN EKOKRITIK DAN RELEVANSINYA SEBAGAI MATERI AJAR SASTRA DI SMA - Ida Ayu Putu Sri Parmini Wati; I Nyoman Yasa; Gde Artawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the story structure of the novel Perempuan yang Menunggu di Lorong Menuju Laut, the author's criticism of the exploitation of nature in the novel Perempuan yang Menunggu di Lorong Menuju Laut, and its relevance as a literary teaching material in high school. The data collection method in this study uses documentation, observation, and interviews. The analysis technique used is a qualitative descriptive analysis technique. The results of this study are three: (1) the story structure of the novel Perempuan yang Menunggu di Lorong Menuju Laut by Dian Purnomo which consists of story facts, themes, literary devices, (2) the author's criticism of the exploitation of nature in the novel Perempuan yang Menunggu di Lorong Menuju Laut by Dian Purnomo which is expressed through the thoughts, attitudes, and behavior of the characters, and (3) its relevance as a literary teaching material in high school which is reviewed for relevance, consistency, and adequacy in the teaching material of Writing Good Practices and Stories About the Environment (Short Stories and Novels).